Trans Palmitoleic acid arises endogenously from dietary vaccenic acid. Issue 3 (15th January 2014) - Jaudszus, Anke; Kramer, Ronny; Pfeuffer, Maria; Roth, Alexander; Jahreis, Gerhard; Kuhnt, Katrin
ABSTRACT: Background: trans Palmitoleic acid ( t -16:1n–7, or 16:1 t 9 in the δ nomenclature usually applied to trans fatty acids and used herein) arouses great scientific interest because it has been suggested to serve as a biomarker for lower risks of type 2 diabetes and coronary artery disease. Objective: Although 16:1 t 9 has been assumed to derive from dietary sources, we examined the hypothesis that 16:1 t 9 might also be endogenously produced from its metabolic precursor vaccenic acid ( t -18:1n–7 or 18:1 t 11). Design: We reevaluated fatty acid data obtained from one human intervention study and one cellular model in both of which 18:1 t 11 was supplemented. Both studies have already been published, but to our knowledge, 16:1 t 9 has not yet been considered. This reanalysis of the datasets was reasonable because a new methodology for identifying 16:1 cis and trans isomers allowed us to address the subject presented in this article. Results: Data showed that the systemic or intracellular increase in 16:1 t 9 was strongly correlated with the increase in 18:1 t 11 after the dietary intake or cellular uptake of 18:1 t 11. The conversion rate in humans was, on average, 17%. Conclusion: Our findings suggest that endogenous 16:1 t 9 is not, as has been assumed, exclusively diet derived but may also be produced by the partial β oxidation of dietary 18:1 t 11.